경량화 프로세스 추적을 통한 중요 데이터 유출 방지 - 강구홍(Koo-Hong Kang) (한국콘텐츠학회 논문지, 9(5), 2009)
As the usage of computers and mobile handsets is popularized, the processing and storing of private and business data are increased. Hence we note that these sensitive data should never be transferred out of these personal devices without user's permission. In this paper, we propose a simple method to prevent transferring the sensitive data out of personal computing devices through their networking interfaces. The proposed method determines which processes invoke open system call related to the sensitive data, and then traces them within a specific duration. The proposed scheme has advantage over the existing ones using authentication or encryption because it could be still working well independent upon the new attack technologies or the latest vulnerabilities of hardware and software. In order to verify the proposed algorithm, we test it by implementing the necessary codes at the user and kernel spaces of Linux. 컴퓨터와 개인 휴대 단말장치 사용의 대중화와 함께 이들 장치들을 이용한 개인정보 혹은 사업상 중요 데이터를 처리하고 저장하는 행위도 따라 증가하게 되었다. 따라서 이들 장치로부터 사용자의 허락 없이 중요 데이터가 자신의 장치로부터 빠져나가는 행위가 일어나서는 안 된다. 본 논문에서는 중요 파일과 관련된 파일 오픈 시스템 콜을 호출하는 프로세스를 일정시간 추적하여 네트워킹 인터페이스를 통해 이들 중요 데이터가 빠져 나가는 것을 방지하는 간단한 방법을 제시하였다. 제안된 방법은 기존 인증 혹은 암호화를 이용한 방법과 비교해 해킹 기술 발전과 하드웨어 및 소프트웨어의 새로운 취약점 발견과 무관하게 안정적으로 동작하는 이점이 있다. 특히, 본 논문에서는 리눅스 환경의 사용자와 커널 영역에서 제안된 알고리즘을 직접 구현하여 타당성을 검증하였다.